Analisis Kualitatif Strategi Pemerintah Daerah dalam Mengoptimalkan Hasil Pengelolaan Kekayaan Daerah untuk Meningkatkan Pendapatan - Ferdy Akbar; Nuh Yabest Sinaga; Nasirwan Nasirwan; Nabila Tijani Tharifah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Regional asset management is a strategic instrument in increasing Local Own-Source Revenue (PAD) and supporting the fiscal independence of local governments in the era of regional autonomy. However, many local governments in Indonesia still face challenges in asset management, such as weak asset inventory systems, limited transparency, insufficient human resource capacity, and the suboptimal utilization of productive assets. This study aims to analyze local government strategies in optimizing regional asset management to increase local revenue. The research employs a qualitative approach using a literature review method through the analysis of academic literature, government regulations, and policy reports related to regional asset management. The results indicate that the optimization of regional assets is strongly influenced by governance quality, supervision systems, policy integration, and innovative asset management strategies such as digitalization of asset information systems, partnerships with the private sector, and performance-based governance implementation. In addition, several issues persist, including weak internal controls and cases of asset management irregularities that may cause regional financial losses. Therefore, strengthening transparency, accountability, human resource capacity, and synergy among government, the private sector, and the community is necessary to achieve optimal, sustainable regional asset management that significantly contributes to increasing PAD and regional development